Determination of Ascorbic Acid Content using the Reverse Phase–High Performance Liquid Chromatography (RP-HPLC) Method - Ismillayli, Nurul; Hermanto, Dhony; Andayani, I. G. A. Sri; Honiar, Ruru; Zuryati, Ulul Khairi; Mariana, Baiq; Shofiyana, Linda Marta (Al-Kimia, 2020)
A method of reverse phase-high performance liquid chromatography (RP-HPLC) was evaluated in ascorbic acid determination. The determination was conducted at optimum conditions for RP-HPLC method, including ethanol as mobile phase, flow velocity of 0.8 mL/min, running time of 5 minutes, injection volume of 10 µL, UV detector, wavelength of 245 nm with internal standard of ascorbic acid in metaphosphate-acetic acid. Result of measurement was validated by AOAC Official Method 967.21. It was obtained that RP-HPLC method was high sensitive and precision method due to its limit of detection was 0,5 µg/mL and RSD was ≤ 2%. The results of the determination of vitamin C content in fresh ceruring fruit using RP-HPLC method and the titrimetry method namely, 52.9057 ± 0.17 and 54.2066 ± 0.87 mg in 100 g sample, respectively. Based on statistical analysis (t-test), there were no significant differences for the two methods used. The percentage of recovery obtained is excellent in the range of 97.9-104.3%. Therefore, the RP-HPLC method is expected to be an accurate method for routine analysis of vitamin C. Key word: ascorbic acid, reverse phase, HPLC, titrimetric. <!--[if supportFields]><![endif]-->